Human Placental Hypoxia-Inducible Factor-1α Expression Correlates with Clinical Outcomes in Chronic Hypoxia in Vivo - Zamudio, Stacy (American Society for Investigative Pathology, 2007)
Placental hypoxia is causally implicated in fetal growth restriction and preeclampsia, with both occurring more frequently at high altitude (>2700 m; HA). The nuclear transcription factor hypoxia-inducible factor (HIF) may facilitate placental oxygen transport at HA by increasing erythropoiesis and placental angiogenesis. We therefore investigated HIF expression and its regulatory mechanisms in placentas from normal pregnancies at high (3100 m), moderate (1600 m), and sea level (75 m) altitudes. Moderate-altitude and sea level placentas did not differ, but HIF-1α and the von Hippel-Lindau tumor suppressor protein were overexpressed in HA placentas. The ability of von Hippel-Lindau tumor suppressor protein to form the E3 ubiquitin protein ligase complex, required for HIF-1α degradation, was unaltered in HA placentas. mRNA for factor-inhibiting HIF, a negative modulator of HIF-1α transactivation, was increased, but protein levels were diminished. Elevated HIF-1α likely contributed to the significant increase we report in HIF-1α downstream target proteins, transforming growth factor β3 in the placenta, and vascular endothelial growth factor and erythropoietin in the maternal circulation. These circulating markers and lowered birth to placental weight ratios correlated with increased HIF-1α, thereby linking molecular and systemic physiological data. The HA response to chronic hypoxia resembles preeclampsia in several aspects, illustrating the utility of the HA model in understanding placental pathologies.